Analysis of Public Knowledge About the Risk of Spreading Infectious Diseases After the Rob Flood Disaster in Sei Naga Lawan Village - Handoko, Fauziah; Susilawati, Susilawati; Wahyuni, Dewi Sri; Syah Putra, Ajib Atha; Siregar, Findyani; Syaharani, Latifah (Universitas Ibn Khaldun Bogor, 2025)
One of the natural disasters that often occur in Indonesia's coastal areas is the Rob flood, which increases the possibility of transmission of infectious diseases in addition to causing damage to infrastructure. The purpose of this study is to examine the general public's awareness of the dangers of infectious disease transmission after the flash flood tragedy in Sei Naga Lawan Village, Perbaungan District. This study uses a quantitative methodology and involves 96 randomly selected respondents. Because there are 2,561 people living in Sei Naga Lawan Village, Perbaungan District, the Slovin formula with an error threshold of 10% is used to calculate the number of samples that need to be studied. Thus, 96 residents is the number of samples to be examined. Based on the research, it was found that out of 96 respondents, 30.2% of respondents had insufficient knowledge in understanding the problem of infectious disease risk, while 69.8% of respondents had quite good knowledge about the problem of infectious disease risk after the flash flood. Poor sanitation and lack of public awareness about prevention can exacerbate infectious diseases such as dengue fever and diarrhea. From the research conducted in the conclusion, most of the respondents (69.8%) felt that they had quite good knowledge about the risk of infectious diseases after the flash flood, although some of them (30.2%) had less knowledge in understanding the problem. This concludes that there is a gap in the public's understanding of health risks. Good education is needed by the community to develop sustainable health knowledge to increase public awareness to prevent infectious diseases after floods appropriately.